2022
DOI: 10.3389/fpubh.2022.1023171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potentially inappropriate medication in older patients with cardiovascular diseases—STOPP/START-based study

Abstract: ObjectiveThis study aims to evaluate the use of STOPP/START criteria in the identification of Potentially inappropriate medication and potential prescribing omissions in older patients with cardiovascular diseases in Bulgaria. Excessive morbidity and mortality has been linked to drug-related problems and increased use of healthcare services and is an understudied problem for Bulgaria.Materials and methodsA prospective, questionnaire-based study was conducted among 543 older patients across 25 pharmacies in Bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In the current investigation, after controlling for several patient-level characteristics, the most important common predictors for PIM use among older men and women were diabetes, ischemic heart disease, anxiety, and polypharmacy. Comorbidities have been cited as contributing factors to using PIM in several published studies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In addition to specific medical conditions, the present study identified a significant association between polypharmacy and higher rates of PIM use.…”
Section: Discussionmentioning
confidence: 99%
“…In the current investigation, after controlling for several patient-level characteristics, the most important common predictors for PIM use among older men and women were diabetes, ischemic heart disease, anxiety, and polypharmacy. Comorbidities have been cited as contributing factors to using PIM in several published studies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In addition to specific medical conditions, the present study identified a significant association between polypharmacy and higher rates of PIM use.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with a prospective cross-sectional study that included 428 patients receiving established treatment for cardiovascular diseases (CVDs). The vast majority of PIMs (31%) were used to treat CVDs, followed by 22.54% used to treat endocrine disorders [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are no studies that have examined PIM usage in older persons with dyslipidemia, despite research among older adults showing a high prevalence of PIM use [ 10 ]. The majority of research [ 13 , 14 , 22 , 23 , 24 , 25 ] involved older persons with cardiovascular illnesses and did not focus specifically on older adults with a cardiovascular risk factor such as dyslipidemia. Recently published articles have emphasized the link between PIM use and cardiovascular diseases [ 13 , 14 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations